Desenvolvimento sustentável à partir da legalização dos bens imobiliários sob a ótica do registro de imóveis: caso de Triunfo - RS - Jorge, Sheila Rüsche (Universidade do Vale do Rio dos Sinos, 2021)
Considering the property right as an axis of sustainable economic development for cities, this research found out that the Property Registry’s institutional activity by sharing its real estate data could provide subsidies to the optimization of public land regularization policies. Such as the reports that identified irregular areas through the number of usucapião, More Legal and Gleba Legal’s demands for a specific geographic region and the ones that identified them through the number of simultaneous owners in the same property tittle. These subsidies could reduce the externalities arising irregular settlements, land tenure regularization’s costs and increase the economy activity by recognizing formal property rights for those who lives in irregular and insecure areas and it could also increase legal property paper’s circulation that would provide access to low costs finance for this low-income population. Consequently, guaranteeing access to human fundamental rights and achieving economic growth based on a regional implementation of 2030’s agenda of OECD’s goals 11 and 16. The research resulted in a Property Registry Office action plan proposal to be validated among the institutions involved in solving land irregularities in Triunfo / RS, Brazilian city nationally representative of the average of land irregularities, which served to collect Property Registry data in order to investigate whether and how the Property Registry office could help solve land problems and help other cities with similar problems. The study’s goal was to find out the means available to identify and treat these land externalities and how the Property Registry could help the institutions involved in the treatment reduce land regularization's costs and social inequalities through the acquisition of property ownership. The research investigated how the precarious urban settlements and others land irregularities could affected transaction costs, property right and sustainable economic development; what were the means available to identify and treat them and how the institutions involved in the treatment could promote wealth circulation and social inequalities reduction through the property right obtained by land tenure regularization. The methodology applied used the inductive method and a systemic approach to Law and Economics by analyzing the legal instruments available for solving these land irregularities and how they affect capital’s generation and sustainable development. The theoretical reference used was Oliver Williamson’s Organizations theory to explain how the transaction costs reduction affects public policies and private businesses. The conclusions reached by the study are as follows: that land irregularities transcend Urban Policy; that property right acquisition, supported in property’s social function, solves others housing, environment and public health problems; that the property right’s recognition to the occupants of irregular area’s increases by 20% up to 32% their family’s per capita income and it also increases by 25% the value of the real estate assets due to more security level of transactions. Consequently, land’s regularization enables lower transaction costs and increases the access to others market and tax collection. Finally, the research concluded that legislation, legal instruments’ correct application, inspection and an assertive and coordinated plan action among the institutions responsible for the land irregularities treatment directly affect the social economic development country degree.
Keywords: Políticas públicas; Loteamentos irregulares; Regularização fundiária; Instituições; Desenvolvimento econômico sustentável; Precarious settlements; Land tenure regularization; Institutions; Sustainable economic development; ACCNPQ::Ciências Sociais Aplicadas::Direito